Implementation of Character Mentoring Program as An Effort To Form Student Morals at SMPII Al Abidin Boyolali - Anna Dwi Rafika; Mohammad Zakki Azzani (MASI Mandiri Edukasi, 2026)
This study aims to describe the implementation of character mentoring programs to foster students' morals, attitudes, and behaviors at SMP Islam Internasional Al Abidin Boyolali. This study uses a descriptive qualitative approach, with data collection through observation, in-depth interviews, and document analysis. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing to understand the process of character mentoring activities comprehensively. The study found that character mentoring was conducted weekly in a cross-generational group of 10-15 students, with a supervisor's assistance. This grouping pattern allows for more intense interaction and a more personalized mentoring process. In its implementation, mentoring does not focus solely on delivering material but also includes a series of activities, namely habituation activities, teacher examples, and continuous mentoring, thus allowing the internalization of Islamic values to occur in a sustained manner. Thus, the program contributes to the formation of student attitudes and behaviors consistent with the values of akhlakul karimah when implemented consistently and supported by the school environment.